(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In this scientific study, the features of the histotopographic structure and morphometric parameters of deep lymph nodes in the neck of baby rats born from female rats receiving a research diet were studied. The results of the study show that rats born from rats that were fed a low-fat diet daily have deep lymph nodes. The dead formation occupies 58.1 % of the area, the primary lymphoid follicular zone – 14.7 %, the medulla – 22.3 %, the paracortical zone – 8.5 %. By the 20-day period, the area of the cavity decreased by 2 times, the primary follicular zone increased (18.3 %), the secondary follicular zone increased (11.6 %), and the paracortical area also increased. Expanded (13.4 %). By the 4-month period, it was observed that follicles and follicles have the same area, the area of secondary follicles increased (19.6 %) compared to primary follicles, and the paracortical follicle occupied 12.1 % of the area.